El lujo como construcción ontológica ambivalente - José Martín Hurtado Galves (Études Caribéennes)
Analysed critically to the luxury as a “concept” to understand it within the ontologising of the subject that consume it and currently holds it. These two categories (consumption and ostentation) distinguish the subject in two ways: first, as someone who seeks to meet needs created from relate consumption to the aestheticisation of both the subject and the world that surrounds it (the object from a sense aestheticizing); second, as someone for whom luxury is supporting reason of relationship and des-relacion with each other. This starting to analyze his form of “speak” ambivalent (bi-directional): luxury says, but also silent; it suggests, but it doesn't impose; opens and closes constantly; limits and extends at a time; in the end, his bivalent way of understanding reality makes it more than a simple way of being in the world.This allows us to explain the reason for the dichotomy of luxury: for some it is unnecessary or superfluous; for others, on the other hand, the luxury is a constant form of asserting itself as imaginary construct. That is clear from an analysis of the luxury as «object» and «idea of object»; watching, well, how that becomes an aestheticisation of ambivalent behaviour movable base. In other words, it is the luxury look but stop looking at the subject who lives «in» and «luxury».